Simultaneous measurement of centre of pressure and centre of mass in assessing postural sway in healthcare workers with non-specific back pain: protocol for a cross-sectional study - Erika Zemkova; Eva Ďurinová; Andrej Džubera; Juraj Chochol; Jana Koišová; Michaela Šimonová; Ludmila Zapletalová (BMJ Open)
Introduction Low back pain (LBP) is widely prevalent in healthcare workers. It is associated with impaired postural and core stability. So far, centre of pressure (CoP) measures have been commonly recorded through the use of a force plate in order to assess postural stability. However, this approach provides limited information about the centre of mass (CoM) movement in the lumbar region in individuals with LBP. Recent developments in sensor technology enable measurement of the trunk motion which could provide additional information on postural sway. However, the question remains as to whether CoM measures would be more sensitive in discriminating individuals with mild and moderate back pain than traditional CoP analyses. This study aims to investigate the sensitivity of CoP and CoM measures under varied stable, metastable and unstable testing conditions in healthcare workers, and their relationship with the level of subjective reported back pain.Methods and analysis This is a cross-sectional controlled laboratory study. A group of 90 healthcare professionals will be recruited from rehabilitation centres within local areas. Participants will complete the Oswestry Disability Questionnaire. The primary outcome will be the rate of their back pain on the 0–10 Low Back Pain Scale (1–3 mild pain and 4–6 moderate pain). Secondary outcomes will include variables of postural and core stability testing during bipedal and one-legged stance on a force plate, a foam mat placed on the force plate, and a spring-supported platform with either eyes open or eyes closed. Both CoP using the posturography system based on a force plate and CoM using the inertial sensor system placed on the trunk will be simultaneously measured.Ethics and dissemination Projects were approved by the ethics committee of the Faculty of Physical Education and Sport, Comenius University in Bratislava (Nos. 4/2017, 1/2020). Findings will be published in peer-reviewed journals and presented at conferences.